2014
DOI: 10.1042/bj20130960
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipids are key modulators of the endocannabinoid-hydrolase FAAH

Abstract: Lipid composition is expected to play an important role in modulating membrane enzyme activity, in particular if the substrates are themselves lipid molecules. A paradigmatic case is FAAH (fatty acid amide hydrolase), an enzyme critical in terminating endocannabinoid signalling and an important therapeutic target. In the present study, using a combined experimental and computational approach, we show that membrane lipids modulate the structure, subcellular localization and activity of FAAH. We report that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 45 publications
4
24
0
Order By: Relevance
“…Also, a recent work identified a possible pathway for substrate binding into FAAH from the membrane side [121]. Despite the absence of the transmembrane helices, the simulations further confirmed that the substrate enters into the active site via the enzymatic "membrane access" cavity, in agreement with previous results [27,119].…”
Section: Enzymatic Mechanism Of Faahsupporting
confidence: 83%
“…Also, a recent work identified a possible pathway for substrate binding into FAAH from the membrane side [121]. Despite the absence of the transmembrane helices, the simulations further confirmed that the substrate enters into the active site via the enzymatic "membrane access" cavity, in agreement with previous results [27,119].…”
Section: Enzymatic Mechanism Of Faahsupporting
confidence: 83%
“…that upregulation of FAAH is related to the down-regulation of CB1 receptors, or if components are altered relatively independent from one another. It has recently been demonstrated that AEA interacting with membrane cholesterol can directly increase FAAH activity (Dainese et al, 2014). It is possible that despite the initial decline AEA levels increase as a consequence of the inflammatory event, and that this constitutive elevation in AEA levels could in turn drive the increase in FAAH activity that persists long after resolution of the inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, conclusions of an ad hoc temporary specialized scientific committee and the fact that phenomena resembling those seen in humans with BIA 10-2474 have not been reported in the literature in any of the numerous animal studies and clinical trials with various inhibitors of FAAH (e.g., PF-04457845, JNJ-42165279, SSR-411298, V-158866 and URB597, just to list those with more advanced programs), strongly (yet not conclusively) suggest that off-target effects of BIA 10-2474 itself or a metabolite thereof, and not FAAH-1 inhibition was the cause of adverse reactions (Mallet et al, 2016; Edan and Kerbrat, 2017). Moreover, it should be recalled that unexpected regulators of FAAH-1 activity are emerging, such as membrane cholesterol that favors the access of AEA to the enzyme active site (Dainese et al, 2014). Thus it remains to be clarified to what extent the lipid environment may tune FAAH-1 activity in vivo , and how it can be exploited to design more effective FAAH-1 inhibitors.…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%